The peculiarities of the sound field energy decay in a room with the use of different pulsed sound sources/Garso lauko energijos slopimo patalpoje ypatumai, naudojant skirtingus impulsinius garso šaltinius - Stauskis, Vytautas (Journal of Civil Engineering and Management, 1999)
The paper deals with the differences between the energy created by four different pulsed sound sources, ie a sound gun, a start gun, a toy gun, and a hunting gun. A knowledge of the differences between the maximum energy and the minimum energy, or the signal-noise ratio, is necessary to correctly calculate the frequency dependence of reverberation time. It has been established by investigations that the maximum energy excited by the sound gun is within the frequency range of 250 to 2000 Hz. It decreases by about 28 dB at the low frequencies. The character of change in the energy created by the hunting gun differs from that of the sound gun. There is no change in the maximum energy within the frequency range of 63–100 Hz, whereas afterwards it increases with the increase in frequency but only to the limit of 2000 Hz. In the frequency range of 63–500 Hz, the energy excited by the hunting gun is lower by 15–30 dB than that of the sound gun. As frequency increases the difference is reduced and amounts to 5–10 dB. The maximum energy of the start gun is lower by 4–5 dB than that of the hunting gun in the frequency range of up to 1000 Hz, while afterwards the difference is insignificant. In the frequency range of 125–250 Hz, the maximum energy generated by the sound gun exceeds that generated by the hunting gun by 20 dB, that by the start gun by 25 dB, and that by the toy gun – by as much as 35 dB. The maximum energy emitted by it occupies a wide frequency range of 250 to 2000 Hz. Thus, the sound gun has an advantage over the other three sound sources from the point of view of maximum energy. Up until 500 Hz the character of change in the direct sound energy is similar for all types of sources. The maximum energy of direct sound is also created by the sound gun and it increases along with frequency, the maximum values being reached at 500 Hz and 1000 Hz. The maximum energy of the hunting gun in the frequency range of 125—500 Hz is lower by about 20 dB than that of the sound gun, while the maximum energy of the toy gun is lower by about 25 dB. The maximum of the direct sound energy generated by the hunting gun, the start gun and the toy gun is found at high frequencies, ie at 1000 Hz and 2000 Hz, while the sound gun generates the maximum energy at 500 Hz and 1000 Hz. Thus, the best results are obtained when the energy is emitted by the sound gun. When the sound field is generated by the sound gun, the difference between the maximum energy and the noise level is about 35 dB at 63 Hz, while the use of the hunting gun reduces the difference to about 20–22 dB. The start gun emits only small quantities of low frequencies and is not suitable for room's acoustical analysis at 63 Hz. At the frequency of 80 Hz, the difference between the maximum energy and the noise level makes up about 50 dB, when the sound field is generated by the sound gun, and about 27 dB, when it is generated by the hunting gun. When the start gun is used, the difference between the maximum signal and the noise level is as small as 20 dB, which is not sufficient to make a reverberation time analysis correctly. At the frequency of 100 Hz, the difference of about 55 dB between the maximum energy and the noise level is only achieved by the sound gun. The hunting gun, the start gun and the toy gun create the decrease of about 25 dB, which is not sufficient for the calculation of the reverberation time. At the frequency of 125 Hz, a sufficiently large difference in the sound field decay amounting to about 40 dB is created by the sound gun, the hunting gun and the start gun, though the character of the sound field curve decay of the latter is different from the former two. At 250 Hz, the sound gun produces a field decay difference of almost 60 dB, the hunting gun almost 50 dB, the start gun almost 40 dB, and the toy gun about 45 dB. At 500 Hz, the sound field decay is sufficient when any of the four sound sources is used. The energy difference created by the sound gun is as large as 70 dB, by the hunting gun 50 dB, by the start gun 52 dB, and by the toy gun 48 dB. Such energy differences are sufficient for the analysis of acoustic indicators. At the high frequencies of 1000 to 4000 Hz, all the four sound sources used, even the toy gun, produce a good difference of the sound field decay and in all cases it is possible to analyse the reverberation process at varied intervals of the sound level decay.Article in Lithuanian.First Published Online: 26 Jul 2012